Diseminasi Elong Ugi Sebagai Media Pembelajaran Penguatan Karakter Siswa Pada Masa Pandemi Covid-19 - Adji Syaifullah; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Elvi Handayani; Vivi Elvira Ekawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The paradigm in learning this year due to the Covid-19 pandemic has resulted in a change in the learning process from onsite to online until now it is used as blended learning. This increasingly dynamic learning change does not close the penetration of culture in the learning process as a form of cultural inheritance to students while simultaneously presenting technology through the application of learning applications such as liveworksheets so that learning is more interesting and meaningful. This service in the form of PKM-PM is carried out as a dissemination to partners, teachers of SMP Negeri 1 Kahu in integrating elong ugi media rich meaningful in live with the aim of strengthening student character education while accommodating meaningful learning. The four stages in the implementation of PKM-PM are observation, pre-training, training, and evaluation. The results of the implementation obtained an increase in the knowledge and skills of teachers in designing, creating and using elong ugi as media in the learning process also using the liveworksheet application to be used in the learning process that can be used online or blended learning.